Pemanfaatan Marketplace Shopee Untuk Menunjang Pemasaran Produk Madu Trigona di Desa Gisting Atas - Junaidah, Junaidah; Saputra, Rasyid; Fanisyah, Elsah (Al-Qalam Institute, 2022)
Community service By utilizing honey bee cultivation fromthe Trigona sp. species, honey bees are used as an additionalbusiness opportunity by utilizing the home page as a placefor honey bee cultivation, and there are not a few people whodeliberately use gardens as a place for cultivation. This isdone to improve the economy and welfare, especially forhoney bee farmers who are members of the